KOMPETENSI GURU DALAM MENGAJARKAN MULTILITERASI DI SEKOLAH DASAR - Imran, Muh Erwinto; Sopandi, Wahyu; Musthafa, Bachrudin; Riyana, Cepi (PD PGMI se Indonesia, 2021)
Competence plays an important role for teachers. It is also emphasized by the government during the performance of their duties. Teachers’ competence is one of the crucial things that they must have in order to teach the students in a class. Based on the results of the questionnaire, it was found that the teachers considered that multiliteracy was something very important as part of the industrial revolution 4.0 era. Multiliteracy is one thing that is competitive in the era of the industrial revolution 4.0 as well as one of the difficult competencies in the 21st century. Multiliteracy is also a competency that must be possessed by students first by a teacher. In Indonesia itself, every student and teacher is very valuable to have multiliteracy skills. The most widely encountered and mastered literacy by teachers is reading/writing literacy. In teaching multiliteracy, teachers face many obstacles, the obstacles they encounter are integrating basic competencies and determining the right model.Thus, every teacher has to learn how to improve their ability and competence. As the front line in the field of education, teachers need to be prepared to acquire qualified competence in teaching skill. One of the ways to ensure teachers’ eligible competence is training. Teacher training is an important key in improving teachers’ competence. The purpose of this study is to analyze the effect of teachers’ training on competence development. This study used a descriptive quantitative design. The object of this research was 261 teachers in Indonesia. The purpose of this study was to analyze the effect of teacher competence.